Educational Strategy for Speech Delay Therapy During The Covid-19 Pandemic - Erwin Purwaningsih (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2022)
Background: Children might be affected by speech delay, which is a sort of developmental problem. The tiny one's speech is delayed in this situation. In a nutshell, speech delay occurs when a child's speech abilities do not develop in accordance with their age. Children with this condition require ongoing diagnosis and treatment. Due to limited access and limits on community activities, Covid-19, which affects the rhythm of human existence, also impacts the type, application, and approach of therapy. Methods: This research is a descriptive study. Following the objectives of the study, research subjects used secondary data from the Global Research on Developmental Disabilities Collaborators, who recognized developmental disabilities in 195 nations during the last 26 years, to meet the study's aims (1990-2016) Results: The number of developmental disorders in children under the age of five years in Indonesia declined between 1990 and 2016, with 1,710,437 cases in 1990 and 1,707. 335 cases in 2016. Indonesia has consistently been in the top ten countries in the world for developmental disability causes. Indonesia ranks fifth in the world in terms of congenital epilepsy, vision loss, and autism, ninth in terms of intellectual disability and ADHD, and seventh in terms of hearing loss. In Indonesia, efforts were made to put limits on communal activities, which are frequently abbreviated as PPKM. The number of incidents that occur in each location, which is classified using the risk zoning map, has an impact on the PPKM level Conclusions: The application of limits on community activities should not prevent children with developmental abnormalities (particularly speech delays) from getting motor development therapy. So that continuous treatment efforts are not inhibited, strategies and innovations must be introduced.